Respuestas

2013-05-10T01:41:30+02:00

Bueno, a resolver.... :D

 

 

2x - \frac{1-3x}{10} - \frac{2}{3} = 2 (x-3) + \frac{1}{5}

 

\frac{20X - 1+3x}{10} = 2 (x-3) + \frac{1}{5} + \frac{2}{3}

 

\frac{20X - 1+3x}{10} = 2 (x-3) + \frac{13}{15}

 

\frac{20X - 1+3x}{10} = \frac{30(X-3)+13}{15}

 

\frac{20X - 1+3x}{2} = \frac{30(X-3)+13}{3}

 

\frac{23X - 1}{2} = \frac{30X-90+13}{3}

 

\frac{23X - 1}{2} = \frac{30X-77}{3}

 

3(23X - 1) = 2(30X-77)

 

69X - 3 = 60X-154

 

69X - 60X = -154 + 3

 

9X = -151

 

X = \frac{-151}{9}  <---- Respuesta.

 

 

 

Listo ahi tienes tu respuesta, Cualquier duda me consultas por mensajes.